The Effect of Varnishing and Soaking on Formability of the AW-5052-H28 Aluminium Alloy Sheets in Erichsen Cupping Test - Krzysztof Żaba; Łukasz Kuczek; Maciej Balcerzak (Advances in Mechanical and Materials Engineering)
This article presents the results of experimental tests on the stretch-forming ability of 0.21-mm-thick AW-5052-H28 aluminium alloy sheets used in the production of pull-off cups. Erichsen test under various tribological conditions (dry friction, lubrication with graphite lubricant) was used to assess the sheet formability. Punches with a various diameter of the spherical end (8 and 20 mm) were used in the tests. The effect of soaking conditions and varnishing variants on the value of Erichsen indices IE and IE11 was investigated. The sheets were soaked for 13 minutes at various temperatures: 185°C, 190°C and 200°C. In test conditions without lubrication, the lowest value of the IE index = 3.3 mm was observed for sheets in as-received state and for samples after soaking. However, the highest values of the Erichsen index in tests without lubrication were measured for varnished samples and repeatedly soaked. The tests conducted under lubrication conditions with graphite grease revealed usually higher values of the IE index compared to testing conditions without the use of grease. The values of the IE11 index were approximately twice lower than the IE indices. Observation of the bulge surface revealed a smooth surface, which means that the material is characterised by a fine-grained microstructure.